UJI EFEKTIFITAS INSEKTISIDA NABATI TERHADAP MORTALITAS Leptocorisa acuta Thunberg. (Hemiptera : Alydidae) PADA TANAMAN PADI (Oryza sativa L.) DI RUMAH KACA - Ahmad Fauzi Syahrial Oemry, Yuswani Pangestiningsih; Syahrial Oemry; Yuswani Pangestiningsih (Universitas Sumatera Utara, 2014)
“The Effectiveness of Botanical Insecticides Test to Mortality the Leptocorisa acuta Thunberg.(Hemiptera : Alydidae) on rice plant in Greenhouse”. The research was held at the Greenhouse OfAgriculture Faculty University of North Sumatera, Medan since June – August 2013. The methodof this research was Completely Randomized Design Non Factorial with 8 treatments and 3replications. Treatments being tested is K0 (control), A1, A2, A3 (25, 50, 75 ml tuba rootextracts/litre of water), T1, T2, T3 (25, 50, 75 ml tobacco extracts/litre of water), and AT (50 mltuba root extracts/litre of water + 50 tobacco extracts/litre of water). The parameters includethe percentage of mortality pest and the death of imago. The result showed that the most effective ofbotanical insecticides was found in treatment AT (100%) at 3 days after application, followed by T3(100%) at 4 days after application and T2 (96,67%) and A3 (95%) at 5 days after application, andless effective was found in A1 (81,67%) and T1 (88,33%) at 5 days after application, and on the 6days after application all botanical insecticides treatmens has show 100% mortality. The death ofimago is the fastest in treatments AT, T3, T2, A3, A2 and T1 occurred at 1 day after planting, andlongest are on treatments A1 occurred at 2 day after planting.Keyword: botanical insectisides, L. acuta, mortality, the time death